Review of the genus Arhaphe (Hemiptera: Heteroptera: Largidae) with descriptions of nine new species from Central America - Stehlík, Jaroslav L.; Brailovsky, Harry (Zootaxa, 2016)
Nine new species of the genus Arhaphe Herrich-Schaeffer, 1850 are described: A. ferruginea sp. nov. from Mexico (Guerrero), A. flavoantennata sp. nov. from Costa Rica (Guanacaste Province), Honduras (Intibuca Department) and Nicaragua (Granada Province), A. hirsuta sp. nov. from Mexico (Oaxaca), A. kmenti sp. nov. from Mexico (Guanajuato, Michoacán), A. longula sp. nov. from Mexico (Guerrero), A. magna sp. nov. from Mexico (Colima), A. myrmicoides sp. nov. from Mexico (Guerrero, Nayarit), A. oaxacana sp. nov. from Mexico (Oaxaca), and A. pilifera sp. nov. from Mexico (Nayarit). The fifth instar larvae of A. arguta (Bliven, 1956), A. carolina Herrich-Schaeffer, 1850, A. cicindeloides Walker, 1873, A. flavoantennata sp. nov., A. mexicana Halstead, 1972, and A. morelensis Brailovsky & Marquez, 1974 are described. Additional state faunistic records of the already described species are provided: A. arguta (Bliven, 1956) (Mexico: Guanajuato, Sonora), A. capitata Halstead, 1972 (Costa Rica; Mexico: Chiapas, Estado de México, Guerrero, Michoacán, Oaxaca, Puebla), A. carolina Herrich-Schaeffer, 1850 (Mexico: Guanajuato, Tamaulipas), A. cicindeloides Walker, 1873 (Mexico: Hidalgo, Querétaro), A. deviatica Brailovsky, 1981 (Nicaragua), A. furcata Brailovsky, 1981 (Mexico: Michoacán), A. halsteadi Brailovsky, 1981 (Mexico: Oaxaca), A. mimetica Barber, 1911 (Mexico: Chihuahua), A. morelensis Brailovsky & Marquez, 1974 (Mexico: Estado de México, Guerrero, Puebla), and A. rustica Brailovsky, 1981 (Mexico: Morelos, Oaxaca).